Addition of Ginseng (Withania Somnifera) To the Diet and Its Effect on Productive Performance for Broilers Raised with Two Different Densities - Al-hamed, Anwar Mohammed; Al-Taie, Anwar Hamdoun (Journal of agricultural, environmental and veterinary sciences, 2021)
The study was conducted to find out the effect of adding ginseng root powder (Withania somnifera) at (0, 1.5 and 3.0) g/kg under two densities of breeding (12 and 17) birds/m2 on performance, economic indicators. Chicks were raised from the age 1 day-42 and distributed to the treatments at the second week in T1:12 bird\m2 +0%, T2:12 bird\m2 +1.5%,T3:12 bird\m2 +0.3%,T4:17bird\m2+0%,T5:17bird\m2+ 1.5%,T6:17 bird \m2 +0.3%.The statistical analysis showed that there was no significant difference in density in body weight, weight gain, relative growth, feed conversion factor, production index, production coefficient,while the density was 12 birds/ m2 superior in consumption The feed density of 17 birds/m2 gave a higher productivity in kg/m2 compared to 12 birds/m2. The addition of ginseng did not affect the weight gain, relative growth, conversion factor, index, production coefficient, productivity yield in kg/m2, while there was a superiority of adding (1.5 and 3.0) g of ginseng compared with no addition in live body weight and in Feed consumption and production factor and in the effect of the interaction there were no significant differences in the weight gain, growth, feed consumption, evidence and production factor, while we note that the interaction(12 birds/ m2+1.5 gm ginseng) gave the highest body weight and a significant improvement in the feed conversion factor for the addition of (1.5 and 3.0) gm under the influence of breeding density 17 birds/m2 and the productivity yield exceeded kg/m2.
Keywords: broiler; density; ginseng; performance; economic indicators